Elbow Ulnar Collateral Ligament Repair With Suture Augmentation Results in Good Clinical Results, a Return-to-Play Rate Between 67% and 93%, and a Postoperative Complication Rate Up to 11.9%: A Systematic Review - Garrett R. Jackson, M.D; Harkirat Jawanda, B.S; Anjay Batra, B.S; Filippo Familiari, M.D; Zeeshan A. Khan, B.A; Christopher M. Brusalis, M.D; Nikhil N. Verma, M.D (Elsevier, 2023)
Purpose: To review the Kerlan-Jobe Orthopaedic Clinic (KJOC) scores, return-to-play rates, and complications after ulnar collateral ligament (UCL) repair with suture augmentation. Methods: A literature search of the PubMed and Scopus databases was conducted on February 17, 2023, using the terms "ulnar collateral ligament," "repair," "internal brace," and "suture augmentation." The search strategy was based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol and included 4 articles published from 2019 to 2022. The inclusion criteria included studies reporting outcomes, return-to-play rates, and/or complications after UCL repair with suture augmentation. The exclusion criteria consisted of non-English language studies, case reports, cadaveric studies, animal studies, letters to the editor, studies with overlapping cohorts, and review articles. The risk of bias was evaluated using the Methodological Index for Non-Randomized Studies (MINORS) criteria. Results: The final analysis included 4 studies with 510 patients (457 male and 53 female patients), ranging in age between 17.8 and 27.5 years, treated with repair and suture augmentation for UCL tears. In this review, we found a mean postoperative KJOC score ranging from 87.9 to 92.6. The overall rate of return to play at the preinjury level or at a higher level than the preinjury level ranged from 67% to 93%; the mean time to return to play ranged from 6.7 to 17.6 months. The postoperative complication rate in this review ranged from 0% to 11.9%. Among the complications, the most common were ulnar nerve paresthesia (range, 0%-8.2%) and postoperative medial elbow pain (range, 0%-3.1%). Overall, the reoperation rate ranged from 0% to 3.4%. No reruptures were reported. Conclusions: UCL repair with the use of suture augmentation results in postoperative KJOC scores ranging from 87.9 to 92.6, a return-to-play rate between 67% and 93%, and a postoperative complication rate up to 11.9%. Level of Evidence: Level IV, systematic review of Level IV studies.